'History from the inside' South African Prisoner-of-War Experience in Work Camp 1169, Dresden, 1943–1945. (October 2014) - Horn, Karen
Abstract : This article narrates the experiences of white English-speaking South African Prisoners-of-War in Dresden Work Camp 1169 during the Second World War. Work Camp 1169 was populated predominantly by South African servicemen, and the availability of their memoirs and diaries, as well as first-hand interviews with some of the former inmates of this camp, provide an opportunity to analyse their experiences in terms of national identity, how well they adapted to captivity and how they managed relationships between themselves, their captors and the German citizens with whom they came into contact.